Análise da formação de um pólo logístico e os recursos humanos como fatores competitivos para a região do grande abc paulista - Sousa, Ana Cláudia Mendes (2007)
This paper aims to present an analysis of the formation of a logistic pole and human resources as competitive factors for the Greater ABC region of São Paulo. The region has undergone several processes of transformation in its economy over the years, and this has been accentuated with globalization, forcing companies to seek new location strategies, which were analyzed in this research. There was divergence of empirical data and opinions of local actors on logistical issues and skilled labor, and it can not be said that there is a difference in relation to other regions of the country. But its development by regionality and its continuous learning process (dynamic learnig region), provides conditions to build an environment favorable to dynamism and innovation, and consequently, regional competitiveness. (AU)